The strategy of developing beef cattle business in Bali Indah farmer groups in Padalembara Village, Poso Regency - Kardi, Fastabikhul Khairatih; Handayani, Sayekti (AgriSains, 2020)
This study aims to determine the right strategy in developing beef cattle breeding business in Bali Indah farmer groups based on regional conditions and availability of livestock production factors in Padalembara Village, Poso Regency. This research has been carried out in Padalembara village, Poso Pesisir Selatan District, Poso Regency, Central Sulawesi in the Bali Indah Farmers Group, December 2019 - January 2020. This research was conducted using a case study method. The case study method is a research method in social science that aims in more detail to explain and understand the object being examined specifically as a research case. This research can be concluded that the position of Bali Indah farmer group is in quadrant V which describe that the farmer group requires the existence of strategy in the form of intensive coaching as an effort to implement strategies to maintain and keep the conditions of internal and external factors. Meanwhile the coaching and accompaniment to farmers will have an impact to increasing the ability of livestock farmers.